Experiment CBL to Strengthen Four OBE Literacies in Automotive Engineering Education: Analysis of the Kirkpatrick Model - Henry Iskandar; Selamat Triono; Siti Ulgari; Safri Gunawan; Dwiki Muda Yulanto; Nur Basuki; Lisyanto Lisyanto (VANOS Journal of Mechanical Engineering Education, 2026)
Graduate learning outcomes should include the current interdisciplinary attitudes, knowledge, and skills needed in the era of technological transformation in the automotive sector. Conducting a CBL model experiment supported by simulation teaching aids to strengthen the 4 four OBE literacies in the automotive control system course. The CBL model includes (engage, investigate, and act) to see perception, knowledge, skills (hard skills and soft skills), satisfaction, and literacy, with Kirkpatrick obtained by using questionnaires and test items conducted by observation methods and written tests. The CBL model, supported by simulation teaching aids and evaluated using the Kirkpatrick framework in automotive control system learning. It is proven that OBE literacy achieves relatively high scores in all four literacy dimensions, with the highest scores in technology literacy (80.4) and data literacy (77.1), followed by human literacy (75.7) and language literacy (73.3). This shows that the four OBE literacies are integrated in higher education.